Predictive Simulation of Wind Turbine Outputs at Mersing, Johor - Salleh, Muhammad Adam Asyraf; Salimin, Suriana (Journal of Electronic Voltage and Application, 2025)
Wind power potential in tropical nations such as Malaysia is typically having low and fluctuating wind speeds, rendering traditional Horizontal Axis Wind Turbines (HAWTs) not as effective. This project solves the dilemma of power output calculation of Vertical Axis Wind Turbines (VAWTs) confidently, which are more appropriate for low-wind regions but for which there are no applicable tools of assessment. This study tries to develop a simulation model that calculates power output of a VAWT based on real environmental readings for example, wind speed, temperature, and relative humidity. Dynamic estimation of power output and air density were included in a working mathematical block model and performed using ideal wind power equation. Environmental readings measured from two Malaysian sites, Batu Pahat and Mersing, were employed in order to explore and test the model. Outputs shows that Mersing whose average wind speed met and exceeded that of turbine cut-in, held up maximum energy output of 34,930 Wh in February, in comparison to Batu Pahat which was likely to fall short of power delivery due to low wind speed. Simulation outcomes also concluded that temperature and humidity significantly influence air density, and hence, turbine efficiency. Lastly, aforesaid proposed model constitutes a certain tool in assessing VAWT viability on the basis of low-wind, high-humidity areas. It upholds early-stage planning, site selection, and early-stage feasibility determination because it provides credible simulations of wind energy output in compliance with changing tropical conditions.